Be a buddy: an exercise in innovation and entrepreneurship - Shana Van Dyck; Luca Fasola; Laura Suorsa; Salla Kunnari; Chamari Dasanayake
Mental health difficulties across university student populations are seen as a serious problem as for universities as well as for their wider communities. Students can search, identify, and evaluate the problems and business opportunities and can come up with new solutions to those problems. During the process of solution search, students might be able to use the development tools and creativity models. The problem is more actual while dealing with students having learning disabilities. Thus, two main solutions were identified: the Emotion Tool and Be a Buddy.
Keywords: Students; Higher Education